High-Frequency Repetitive Sensory Stimulation as Intervention to Improve Sensory Loss in Patients with Complex Regional Pain Syndrome I - David, Marianne; Dinse, Hubert R.; Mainka, Tina; Tegenthoff, Martin; Maier, Christoph (Frontiers in Neurology, 2015)
Achieving perceptual gains in healthy individuals, or facilitating rehabilitation in patients is generally considered to require intense training to engage neuronal plasticity mechanisms. Recent work, however, suggested that beneficial outcome similar to training can be effectively acquired by a complementary approach in which the learning occurs in response to mere exposure to repetitive sensory stimulation (rSS). For example, high-frequency repetitive sensory stimulation (HF-rSS) enhances tactile performance and induces cortical reorganization in healthy subjects and patients after stroke. Patients with complex regional pain syndrome (CRPS) show impaired tactile performance associated with shrinkage of cortical maps. We here investigated the feasibility and efficacy of HF-rSS, and low-frequency rSS (LF-rSS) to enhance tactile performance and reduce pain intensity in 20 patients with CRPS type I. Intermittent high or low frequency electrical stimuli were applied for 45min/day to all fingertips of the affected hand for 5 days. Main outcome measures were spatial 2-point-discrimination thresholds and mechanical detection thresholds measured on the tip of the index finger bilaterally. Secondary endpoint was current pain intensity. All measures were assessed before and on day 5 after the last stimulation session. HF-rSS applied in 16 patients improved tactile discrimination on the affected hand significantly without changes contralaterally. Current pain intensity remained unchanged on average, but decreased in 4 patients by 30%. This limited pain relief might be due to the short stimulation period of 5 days only. In contrast, after LF-rSS, tactile discrimination was impaired in all 4 patients, while detection thresholds and pain were not affected. Our data suggest that HF-rSS could be used as a novel approach in CRPS treatment to improve sensory loss. Longer treatment periods might be required to induce consistent pain relief.